Condition of the autonomic nervous system during the 'sit-stand-sit' orthostatic test in university students in areas of military conflict in Ukraine - Igor Vypasniak; Sergii Iermakov; Lyudmila Shesterova (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Extended residence in a zone of military conflict presents health risks for students. Hence, this research focuses on evaluating the condition of the autonomic nervous system among university students residing in Ukraine's conflict-affected areas.